Self-assessment tax system: Survey evidence from the academicians, UiTM Shah Alam / Norazah Md Azali - Md Azali, Norazah (2006)
The implementation of the self-assessment tax system (SAS) by the Inland Revenue Board Malaysia (IRB) for salaried individual taxpayers in the year of assessment 2004 requires the taxpayers to compute their own tax liabilities. Hence, the taxpayers must have a certain level of tax knowledge and tax literacy in discharging hislher duties as a taxpayer. At the time of this study, little is known about the tax literacy and experience of non-accounting academicians in completing the tax return form in the era of SAS. In response, this study has emerged to fill a research gap. This study aims to i) assess the tax knowledge of the non-accounting academicians in UiTM ii) examine the nonaccounting academicians' response towards the implementation of the self-assessment tax system and iii) seek the opinions from the non-accounting academicians on the introduction of tax education in their faculties A survey was used to collect the data from 6 non-accounting faculties at the Universiti Teknologi MARA Shah Alam campus. 685 questionnaires were distributed and the response rate was 27.3% (187/685). The findings indicate that most of the respondents were aware of the implementation of SAS and about 580/0 of the respondents had a high level of understanding of the concept of SAS. The findings revealed that the respondents were in favour of a tax subject be introduced at their faculties. The findings of the study will enable the authorities to review the tax education program in higher learning institutions. Essentially, this study provides useful insights for the UiTM management on the importance oftax subjects to be introduced in educating the non-Accounting students who are the future taxpayers. IX COPYRIGHT ©